Multi-objective optimization of distribution network reconfiguration considering adjusting the output of distributed generation - Wang, Shao-Lin; Tang, Wei; Bai, Mu-Ke; Lu, Tao; Zhang, Li-Mei; Guan, Hong-Hao (Dianli Xitong Baohu yu Kongzhi, 2012)
Distribution network reconfiguration can improve the operation economy and safety of the network, while distributed generation injected to distributed network directly affects flow distribution and has a greater impact on network reconfiguration. Considering the impact of distributed generation on network reconfiguration, this paper makes switch status and DG output as the optimization variables, and establishes a multi-objective optimization model which takes network loss and load balancing rate as the objective functions. The paper puts forward a multi-objective mixed optimization method combining spanning tree and ant colony algorithm with genetic algorithm, which realizes the collaborative optimization of distributed network structure and DG output. This method uses ant colony algorithm based on spanning tree to reconstruct the distribution network in order to guarantee the network topology constraint, and uses genetic algorithm based on Pareto dominance to optimize the output of DG output. Simulation res